School Climate in Improving Conducive Learning Quality in MIN 2 Sibolga - Syafaruddin, Syafaruddin; Salim, Salim; Pasaribu, Zulfikar (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
School climate is â€œheartâ€ and â€œbreathâ€ in a school. It relates to all interaction components among school members from culture, social until the harmonization of the learning environment which affects the output quality. This study discusses the school climate in increasing learning quality in MIN (State Islamic Primary School) 2 Sibolga. The scope of the study focused on how to produce a school climate and its role in improving learning quality in MIN 2 Sibolga. This study applied the qualitative approach and school activities as the object of the study, such as daily routine, programmed activities, and self-development activities. The result of the study showed that a â€œconduciveâ€ school climate was created well in MIN 2 Sibolga, it could be seen from (1) creating a conducive learning climate, (2) managing school environment, (3) developing school psychologic-cultural routines, and (4) improving â€œdisciplineâ€ culture for school members. However, there were some obstacles, such as inadequate infrastructure, low teacher competence, less financing, less student development, and lack of training for the teachers.